RELATIONSHIP MARKETING: STUDI TENTANG PENGARUH KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP LOYALITASKONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi pada PT. Lautan Berlian Utama Motor) - Putu Tia Anggreni; Nur Efendi; Prasetya Nugeraha (Jurnal Kompetitif Bisnis, 2022)
Abstract Purchase decisions of consumers shopping at Untung Suropati Traditional Market can be analyzed from the influence of price, service quality and servicecape partially and simultaneously. The type of research used is explanatory research with a quantitative approach. The population in this study were people who shopped at Untung Suropati Market in Bandar Lampung with a total sample of 100 respondents who were determined by the purposive sampling. The data analysis technique uses simple regression analysis and multiple regression analysis with the SPSS 25 program test tool. Based on the F (simultaneous) test, it shows that the variable price, service quality, and servicescape have a significant effect on purchasing decisions in traditional markets with a coefficient of determination of 52.8% partially shows that the variables of price, service quality and servicescape have a positive and significant influence on purchasing decisions in the traditional market of Untung Suropati Labuhan Dalam.